ANALYSIS OF ACTIVE FAMILY PLANNING PARTICIPANTS AND OPERATIONAL FIELD ACTIVITIES IN SURABAYA IN 2019 - Rafika Diyah Arafah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Surabaya, as a provincial capital, carries a big burden in population control. Besides the issue of incoming migration, it is also influenced by population growth due to fertility. Implementing family planning programs can serve as a solution to control the population. This study aimed to analyze the data trends of active family planning participants and operational field activities related to family planning in the city of Surabaya in 2019. Secondary data were sourced from the monthly publication of the East Java BKKBN, namely the Hasil Analisis dan Evaluasi Program Kependudukan Keluarga Berencana dan Pembangunan Keluarga (KKBPK) Program in 2019. The data used included  active family planning participants and field operational activities which are operational data of car movements for services, coordination meetings, mobile family planning teams, and outreaches to Field Advisors of Family Planning / Petugas Lapangan Keluarga Berencana (PLKB) or Penyuluh Keluarga Berencana (PKB), and IEC conducted by religious or community leaders. The data comprised of participants’ activeness in  family  planning  activities  and  operational  field  activities in Surabaya from January to December in 2019. Descriptive analysis methods were used to explain trends in data. The data had the same pattern for both active participants and operational field activities in the final quarter. The trend of active family planning participants increased by 2.3% from January to December 2019, but the trend of field operational data decreased by 11.6%, 9.35%, 9.35%, 6.45%, and 8.03%.